1987
DOI: 10.1177/001440298705400210
|View full text |Cite
|
Sign up to set email alerts
|

Holland Personality Types among Learning Disabled and Nonlearning Disabled High School Students

Abstract: Many learning disabled adults are not as successful vocationally as nonhandicapped adults. One reason for their lack of success may be that they are working in occupations incongruent with their personalities and interests. While nonhandicapped individuals are considered to have a variety of occupational interests, learning disabled persons are often occupationally stereotyped and trained for and placed into a more limited variety of occupational environments. The study described in this article investigated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
1
6
0
1
Order By: Relevance
“…These research studies indicate that many youth and adults with LD are generally not doing well once they leave school and may have considerable difficulty finding and retaining employment. This conclusion supports research by Sitlington (1981) and Cummings and Maddux (1987) data that many adults with LD may be employed in occupations not suited to their abilities, interests, and personalities. This conclusion supports research by Sitlington (1981) and Cummings and Maddux (1987) data that many adults with LD may be employed in occupations not suited to their abilities, interests, and personalities.…”
supporting
confidence: 88%
“…These research studies indicate that many youth and adults with LD are generally not doing well once they leave school and may have considerable difficulty finding and retaining employment. This conclusion supports research by Sitlington (1981) and Cummings and Maddux (1987) data that many adults with LD may be employed in occupations not suited to their abilities, interests, and personalities. This conclusion supports research by Sitlington (1981) and Cummings and Maddux (1987) data that many adults with LD may be employed in occupations not suited to their abilities, interests, and personalities.…”
supporting
confidence: 88%
“…Differences between ethnic groups have been found, yet they have tended to be small (Davison Aviles & Spokane, 1999). Some researchers have suggested that learning disabled youngsters have lower career interest scores because of a restriction in life experiences (Winer, Pierce, & Wilson, 1988), whereas others have shown that learning disabled and nonhandicapped high school students are similar in terms of Holland interests (Cummings & Maddux, 1987a).…”
Section: Holland's Career Interest Theorymentioning
confidence: 99%
“…Although research has demonstrated that students with learning disabilities do not differ from students without learning disabilities in terms of occupational interests and Holland personality types (Cummings & Maddux, 1987). individuals with learning disabilities consistently work in jobs that are not suited to their abilities and characteristics (Sitlington, 1981).…”
Section: Career Maturity Among Individuals With Learning Disabilitiesmentioning
confidence: 99%